How does paternal involvement during marital conflict contribute to young children's socioemotional outcomes? - Karan, Rümeyza Pınar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
The family is a system in which each existing relationship, such as mother-father or father-child, affects each other. Past research has shown that marital conflict negatively impacts fathers' engagement, their direct care activities, and children's socio-emotional adjustment. No study has yet examined children's socio-emotional adjustment by examining the combination of marital conflict and paternal involvement. The present study is in the scope of a representative project called “Socio-cultural and Psychological Antecedents and Consequences of Child-rearing Styles Across Generations and Developmental Stages in Turkey" and investigated the relationship between these variables as well as the role of marital conflict on toddlers' socio-emotional adjustment in the combination of low and high paternal involvement. Mothers with children aged 13-40 months (699 boys, 676 girls) participated in the study. They completed a comprehensive demographic form, marital conflict, paternal involvement (i.e., paternal engagement and paternal care), toddlers' social-emotional adjustment, and mother involvement scales. Hierarchical regression analyses showed that maternal involvement and marital conflict uniquely contribute to paternal engagement and care. Additionally, marital conflict has a unique contribution to toddlers' behavioral problems. Likewise, paternal engagement and care in total have a relatively main effect on toddlers' social competence. There was an interaction between paternal engagement and marital conflict such that the relationship between marital conflict and toddlers' social competence was significant only when paternal engagement was high.
Keywords: Marital psychotherapy.; Child rearing.